REFLEKSI HUT LVRI DALAM PENGUATAN KETAHANAN SOSIAL DAN NILAI KEJUANGAN DI KOTA BENGKULU - Oktrina Syafriantini; Jasmani (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This study aims to examine the social contribution of LVRI Bengkulu Province in responding to disaster situations on the island of Sumatra in relation to the theme "With the Spirit of Togetherness, LVRI Cares for Disasters and Moves Forward in Struggling with the People to Build the Country Towards a Golden Indonesia." This study applies a qualitative approach and was conducted in Bengkulu City by making the DPD LVRI Bengkulu as the main object of the study. The data collection process lasted for two months, namely from December 2025 - January 2026. This study concluded that LVRI Bengkulu Province has a real, strategic, and relevant social contribution in responding to disaster situations on the island of Sumatra. The commemoration of LVRI's anniversary with the theme of togetherness and disaster awareness is a strategic medium to strengthen social integration, build public trust, and foster national character across generations